2021
DOI: 10.3389/pore.2021.1609846
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Fusobacterium nucleatum Infection and Regulatory T Cell Enrichment in Esophageal Squamous Cell Carcinoma

Abstract: A variety of pathogenic microorganisms promote tumor occurrence and development through long-term colonization in the body. Fusobacterium nucleatum (F. nucleatum) is abundant in precancerous esophageal lesions and is closely related to the malignant progression of esophageal squamous cell carcinoma (ESCC). The invasion of exogenous microorganisms can reshape the immune microenvironment, make the immune system incapacitated, and assist tumor cells in immune escape. A variety of pathogenic microorganisms induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Intratumor microbiota can affect tumour progression and metastasis through inducing DNA damage and driving oncogenic pathways [ 27 ], which are associated with poor prognosis. Microbiota in tumour can also generate an immune suppressive microenvironment by recruiting immunosuppressive cells, leading to tumour immune escape [ 29 , 30 ]. For example, Streptococcus gallolyticus can inhibit T cells by recruiting myeloid-derived suppressor cells (MDSCs), tumour-associated macrophages (TAMs) and dendritic cells (DCs) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intratumor microbiota can affect tumour progression and metastasis through inducing DNA damage and driving oncogenic pathways [ 27 ], which are associated with poor prognosis. Microbiota in tumour can also generate an immune suppressive microenvironment by recruiting immunosuppressive cells, leading to tumour immune escape [ 29 , 30 ]. For example, Streptococcus gallolyticus can inhibit T cells by recruiting myeloid-derived suppressor cells (MDSCs), tumour-associated macrophages (TAMs) and dendritic cells (DCs) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study confirmed that immunosuppressive regulatory T (Treg) cells were enriched in Fn-infected ESCC tissues. Moreover, a high abundance of Treg cells can cause antitumour immune inactivation [ 3 ]. These results suggest that Fn-mediated remodelling of the tumour immune microenvironment may promote the development of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were restained with haematoxylin (Solarbio), dehydrated with ethanol, cleared with xylene, and sealed with neutral gum. Refer to the manufacturer’s instructions and literature for the specific experimental steps [ 3 ]. The colocalization of CD8 and KIR2DL1 expression in two serial sections were observed by randomly selecting 5 (400×) fields of view with an optical microscope (Nikon).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top-ranked KEGG pathway in F. nucleatum -positive esophageal cancer was the “cytokine–cytokine receptor interaction”, thereby supporting the possible mechanism that F. nucleatum might contribute to the aggressive tumor behavior through the activation of chemokines, such as CCL20 ( 47 ). The infection and colonization of F. nucleatum might also facilitate the immune escape of tumor cells and weaken the antitumor immune response through enriching Treg cells, assisting the long-term self-colonization, and promoting the malignant progression of ESCC ( 50 ). In addition, 13 samples of F. nucleatum -positive ESCC were analyzed by the whole-exome sequencing and the results showed that the function of the mutant gene was mainly concentrated in the pathways regulating apoptosis and the epidermal growth factor-like protein domain ( 49 ).…”
Section: F Nucleatum In Esophageal Cancermentioning
confidence: 99%